Patients with Severe Poststroke Fatigue Show a Psychosocial Profile Comparable to Patients with Other Chronic Disease: Implications for Diagnosis and Treatment. (9th November 2011) - Zedlitz, Aglaia M. E. E.; Visser-Meily, Anne J. M. A.; Schepers, Vera P.; Geurts, Alexander C. H.; Fasotti, Luciano
Abstract : Objective . To obtain a psychosocial profile of patients with poststroke fatigue (PSF), which could aid in optimizing treatment strategies. Methods . Eighty-eight outpatients with severe PSF measured with the Checklist Individual Strength-fatigue subscale (CIS-f) and the Fatigue Severity Scale (FSS) were selected. Depression and anxiety, psychological distress, coping, social support, and self-efficacy of this group were compared to reference groups of healthy controls and patients with other chronic diseases. Associations between psychosocial characteristics and fatigue were calculated. Results . Compared to healthy controls, patients with PSF reported more psychological distress, less problem-focused coping, and more positive social support. Minor or no differences were found in comparison with other chronic patients. The CIS-f correlated with somatic complaints and the FSS with cognitive complaints. Conclusion . Patients with PSF show a psychosocial profile comparable to patients with other chronic disease. Implications for diagnosis and treatment are discussed.